2012
DOI: 10.1016/j.celrep.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Adult Neurogenesis Is Maintained by Neil3-Dependent Repair of Oxidative DNA Lesions in Neural Progenitor Cells

Abstract: Accumulation of oxidative DNA damage has been proposed as a potential cause of age-related cognitive decline. The major pathway for removal of oxidative DNA base lesions is base excision repair, which is initiated by DNA glycosylases. In mice, Neil3 is the main DNA glycosylase for repair of hydantoin lesions in single-stranded DNA of neural stem/progenitor cells, promoting neurogenesis. Adult neurogenesis is crucial for maintenance of hippocampus-dependent functions involved in behavior. Herein, behavioral stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 43 publications
(54 reference statements)
5
87
0
2
Order By: Relevance
“…At the cellular level, loss of BER of oxidative lesions is associated with in impaired proliferation of neurospheres from Polb À/À and Neil3 À/À mice (Sugo et al, 2000;Regnell et al, 2012). In our experiments, NSPC cultures derived from hMTH1-Tg mice proliferated better than those from wild-type animals, suggesting that enhanced protection against oxidative damage provides a proliferative advantage.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…At the cellular level, loss of BER of oxidative lesions is associated with in impaired proliferation of neurospheres from Polb À/À and Neil3 À/À mice (Sugo et al, 2000;Regnell et al, 2012). In our experiments, NSPC cultures derived from hMTH1-Tg mice proliferated better than those from wild-type animals, suggesting that enhanced protection against oxidative damage provides a proliferative advantage.…”
Section: Discussionmentioning
confidence: 47%
“…hMTH1 overexpression increases the proliferative capacity of adult neural stem/progenitor cells As BER-defective mice (Polb À/À and Neil3 À/À mice) may show altered neurogenesis (Sugo et al, 2000;Regnell et al, 2012), we investigated whether hMTH1 overexpression provided some neurogenic advantage. To this end, we assessed the formation of neurospheres generated by adult neural stem/progenitor cells…”
Section: Increased Hmth1 Expression Enhances Exploration Of Environmementioning
confidence: 99%
“…[29,30] NEIL3-null mice showed learning and memory deficits and reduced anxiety-like behavior, and synaptic irregularities in hippocampal neurons. [31] All together, these results suggest that NEIL3 may have a specific role in neurogenesis in the central nervous system. The NEIL3 has been shown to be highly expressed in many tumor tissues, which supports the notion that NEIL3 might be associated with proliferation capacity.…”
Section: Neil3 Expression Patternsmentioning
confidence: 78%
“…NEIL3-null mice also showed learning and memory deficits and reduced anxiety-like behavior, and synaptic irregularities in hippocampal neurons. [31] Future studies addressing the role of NEIL3 in neuronal tissue in ischemic stroke will shed more light on this issue.…”
Section: Neil3mentioning
confidence: 99%
“…In mice, Neil3 is found to be highly expressed in hematopoietic tissue and testis, during embryonic development and in progenitor rich regions in the brain, while human NEIL3 is found to be highly expressed in thymus, testis and in multiple forms of cancer [28][29][30][31][32]. Recently, we showed that murine Neil3 is important for maintenance of cognitive performance [33] and regeneration of neural tissue after perinatal hypoxia-ischemia [32], indicating a role of Neil3 in neurogenesis and protection against hypoxiainduced tissue damage. Thus, several studies indicate a role for NEIL3/Neil3 during cell proliferation, and it is therefore not clear whether canonical repair of oxidative DNA base lesions is the only function of NEIL3.…”
Section: Discussionmentioning
confidence: 97%